Rapid Diagnosis of Mycobacterium marinum Infection by Next-Generation Sequencing: A Case Report - Xing, Fanfan; Lo, Simon K. F.; Ma, Yuanchao; Ip, Jonathan Daniel; Chan, Wan-Mui; Zhou, Meixun; Gong, Miaozi; Lau, Susanna K. P.; Woo, Patrick C. Y. (Frontiers in Medicine, 2022)
We present the first report of histology- and culture-proven Mycobacterium marinum infection diagnosed by next-generation sequencing (NGS). It took less than 2 days to make a microbiological diagnosis using the Oxford Nanopore Technologies’ MinION device, compared to 20 days for the mycobacterium to be isolated from the tissue biopsy. NGS is particularly useful for culture-negative and slow-growing microorganism infections, such as mycobacterial, fungal and partially treated pyogenic bacterial infections. Due to its low equipment cost, short turn-around-time and portable size, the Oxford Nanopore Technologies’ MinION device is a useful platform for NGS in routine clinical microbiology laboratories.